Inter-state migrant workmen (regulation of employment and conditions of service) act, 1979 - Universal (Gurgaon LexisNexis, 2023)
This book is about the inter-state migrant workmen (regulation of employment and conditions of service) act, 1979 (30 of 1979).
Keywords: Bare act